2006
DOI: 10.1021/jp056158t
|View full text |Cite
|
Sign up to set email alerts
|

Ion−Neutral Potential Models in Atmospheric Pressure Ion Mobility Time-of-Flight Mass Spectrometry IM(tof)MS

Abstract: The ion mobilities and their respective masses of several classes of amines (primary, secondary, and tertiary) were measured by electrospray ionization atmospheric pressure ion mobility time-of-flight mass spectrometry IM(tof)MS. The experimental data obtained were comparatively analyzed by the one-temperature kinetic theory of Chapman-Enskog. Several theoretical models were used to estimate the collision cross-sections; they include the rigid-sphere, polarization-limit, 12-6-4, and 12-4 potential models. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Mobility in mixtures is predicted by Blanc’s law, and shows that small amounts of polar gases can prevent the expected hard sphere mobility coefficients from being observed. For instance, the comprehensive drift gas IMS results from the Hill group 14 scale for each ion as expected with reduced mass for several drift gases, but not to the full extent predicted for helium, while low pressure, fully-declustered experiments by Bierbaum and Leone 15 do scale as expected, showing the very high mobility in helium of 11.8 cm 2 /V·s for C 6 H 6 + . This polar-nonpolar mixing effect has also been examined for t-C 4 H 9 + in Ref 16 .…”
Section: Resultsmentioning
confidence: 66%
“…Mobility in mixtures is predicted by Blanc’s law, and shows that small amounts of polar gases can prevent the expected hard sphere mobility coefficients from being observed. For instance, the comprehensive drift gas IMS results from the Hill group 14 scale for each ion as expected with reduced mass for several drift gases, but not to the full extent predicted for helium, while low pressure, fully-declustered experiments by Bierbaum and Leone 15 do scale as expected, showing the very high mobility in helium of 11.8 cm 2 /V·s for C 6 H 6 + . This polar-nonpolar mixing effect has also been examined for t-C 4 H 9 + in Ref 16 .…”
Section: Resultsmentioning
confidence: 66%
“…It is quite clear that for a monomer and a dimer with the same reduced mass, the monomer has a lower reduced mobility and therefore a larger collision cross section than that of the dimer. It has previously been shown that the motion of ions in nitrogen at 200°C, where cluster formation is minimal [22], can be described by the rigid sphere model [23]. Our experiments were performed at ambient temperature, where the mobility is expected to be influenced by cluster formation, especially with the water ubiquitously present.…”
Section: Resultsmentioning
confidence: 96%
“…The polarizability of the helium gas molecule leads to a potential that scales with 1/r 4 , where r is the distance between the point charge (ion) and the induced dipole (gas molecule). This means that the measured collision cross section for very small ions is governed mainly by the attractive interaction due to gas polarizability, rather than by the repulsive interaction due to collisions, which is determined by the van der Waals radii of the silver cluster and the He molecule (Tammet 1995;Gilb et al 2002;Steiner et al 2006). The shift in mobility for the first peak was also observed by Weis et al (2002) who measured the first peak at 30.5 A 2 (Z ¡1 D 0.0523 Vs cm ¡2 ) while the calculated theoretically expected value was 20.8 A 2 (Z ¡1 D 0.0357 Vs cm ¡2 ).…”
Section: Results and Discussion Silver Cluster: Identification Of Clumentioning
confidence: 99%